Moxifloxacin-associated neutropenia. (May 2013) - Berk, Veli; Demiraslan, Hayati; Berk, Elife; Karaca, Halit; Inanc, Mevlude; Bozkurt, Oktay; Ozkan, Metin
Abstract A 32-y-old woman presented with pneumonia. Treatment was started with moxifloxacin. On day 2 of moxifloxacin treatment the patient developed neutropenia. After discontinuing the moxifloxacin, neutrophil counts were normal on day 4. Clinicians should be aware of the possibility of this adverse effect in patients treated with moxifloxacin.